Estresse térmico no acúmulo de prolina livre de plântulas de guandu oriundas de sementes tratadas com poliaminas - Silva, Jessica da (2015)
It was studied the effects of seed treatment with polyamines of pigeonpea for proline content of seedling in order to verify that the application of these polyamines attenuates temperature stress on germination and early seedling growth, and see if exogenous putrescine and spermidine induce the accumulation of proline, this amino acid may be biochemical and physiological indicator in seedlings that are under suboptimal temperatures and supraoptmail. The seeds of pigeonpea cv. BRS Mandarin and cv. Caqui, treated with a solution of 0.5 mM of putrescine and spermidine, were subjected to suboptimal temperature (20 degrees C, 18 degrees C, 16 degrees C and 14 degrees C) and supraoptimal (36 degrees C, 38 degrees C, 40 degrees C and 44 degrees C) for 24 hours and 48 hours. After these periods, were subjected to 25 degrees C until day 10, when the percentage of seed germination were observed, the proline content of vegetative parts and the dry mass of the seedlings. A completely randomized design in a factorial arrangement was used 3x4x2+3 (solutions with polyamines, temperature stress by cooling/heating, time of exposure to stress, plus additional factors em25 degrees C with 0.0 mM and 0.5mM of Put and Spd), with four replicates of 25 seeds. The results were submitted to analysis of variance and means were compared by Tukey test at 5% probability, separately for each cultivar. Both exogenous polyamines attenuate the effects of cooling and heating, contributing to the growth of germinated seeds. Also, putrescine and spermidine exogenous mitigated the adverse effects by inducing proline accumulation, which leads to osmotic adjustment temperatures, although this physiological response has not minimized the negative effects of temperature stress on seedling growth of pigeonpea. Proline can be considered biochemical and physiological indicator in seedlings of both cultivars of pigeonpea treated with polyamines under temperature stress.